Variations in the volume fraction of hybrid composites reinforced with bamboo fiber and fiber-glass fiber influence the Tensile and Impact tests - Yasir Amani Yasir Amani; Ferri Safriwardy; Akbar Gultom; Faisal Muhammad Nur; Heindrix Hidayat (Journal of Mechafa Engineering and Fabrication, 2026)
This research is to create a prototype plastic composite reinforced with bamboo fiber and fiber-glass with variations in volume fraction 25% SB : 25% FG, 35% SB : 15 % FG and 40% SB: 10% FG, the fiber layer types are arranged in the longitudinal direction (0°) with random laminate orientation, for the matrix using BTQN 157 EX polyyester resin. test specimens using the hand lay up method. Composite testing is in the form of Tensile testing referring to Standard ASTM D638-14 and Impact Testing referring to ASTM D6110-10 using the charpy method. The results in the optimal tensile test were greatest at a volume fraction of 40% SB :15% FG with an average tensile strength value of = 80.907 MPa, strain ϵ = 2.53% and elastic modulus E = 31.96 MPa. The lowest tensile strength is at a volume fraction of 35% SB:10% FG with an average value of σ =75.552 Mpa. strain ϵ = 2.09 % and elastic modulus 36.01 MPa. In the charpy impact test, the highest volume fraction was at 35% SB :15% FG with impact strength (HI) = 0.83 . Absorbed energy (EI) = 46.73 Joules. The lowest impact strength is at a volume fraction of 35% :15% with impact strength (HI) = 0.24 . Absorbed energy (EI) = 30.94, However volume fraction 40%:10% Impact Strength (HI) = 0.79 . However, the highest absorbed energy (EI) = 64.16 Joules. The observation results show that the fiber volume is good at a percentage of 40% SB with 15% FG suitable for combining as an alternative tensile material. To observe the fracture results of the Impact test specimen, pull-out fiber was found. However, composites reinforced with bamboo fiber have strong enough capabilities for manufacturing product applications